Soft Tissue Augmentation with Silk Composite Graft - Park, Yong-Tae (Maxillofac Plast Reconstr Surg, 2014)
PURPOSE: The objective of this study was to evaluate the interaction between 4-hexylresorcinol (4HR) and antibody as that affects the performance of a silk-4HR combination graft for soft tissue augmentation in an animal model. METHODS: The silk graft materials consisted of four types: silk+10% tricalcium phosphate (TCP) (ST0), silk+10% TCP+1% 4HR (ST1), silk+10% TCP+3% 4HR (ST3), and silk+10% TCP+6% 4-HR (ST6). The antibody binding assay tested the 4HR effect and scanning electron microscopic (SEM) exam was done for silk grafts. The animal experiment used a subcutaneous pocket mouse model. The graft – SH0 or SH1 or SH3 or SH6 – was placed in a subcutaneous pocket. The animals were killed at one, two, and four weeks, postoperatively. The specimens were subjected to histological analysis and lysozyme assay. RESULTS: Groups with 4HR applied showed lower antibody binding affinity to antigen compared to groups without 4HR. In the SEM examination, there was no significant difference among groups. Histological examinations revealed many foreign body giant cells in ST0 and ST1 group at four weeks postoperatively. Both ST3 and ST6 groups developed significantly lower levels of giant cell values compared to ST0 and ST1 groups (P <0.001) at four weeks postoperatively. In the lysozyme assay, the ST1 and ST3 groups showed denser signals than the other groups. CONCLUSION: 4HR combined silk implants resulted in high levels of vascular and connective tissue regeneration.